2001
DOI: 10.1093/rheumatology/40.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 promoter polymorphism (-174 G/C) in Caucasian German patients with systemic lupus erythematosus

Abstract: The IL-6 promoter polymorphism --174 G/C does not contribute significantly to disease susceptibility, but predisposes to distinct clinical and immunological features. A genetically determined high IL-6 response may have a pathogenic role under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
3
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 41 publications
1
56
3
2
Order By: Relevance
“…The frequency of the C allele in healthy Caucasians is 48%. 7,8 Several studies showed conflicting results regarding the effect of 2174G/C IL-6 polymorphism on plasma CRP or IL-6 levels and cardiovascular risk factors. Brull et al 9 have shown that patients carrying !1C allele of the 2572G/C and 2174G/C IL-6 polymorphisms had significantly higher IL-6 levels six hours after CABG.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the C allele in healthy Caucasians is 48%. 7,8 Several studies showed conflicting results regarding the effect of 2174G/C IL-6 polymorphism on plasma CRP or IL-6 levels and cardiovascular risk factors. Brull et al 9 have shown that patients carrying !1C allele of the 2572G/C and 2174G/C IL-6 polymorphisms had significantly higher IL-6 levels six hours after CABG.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This is in keeping with clinical findings that high serum IL-6 correlates with active disease and fever. [3][4][5] Since our first report, this variant has been associated with numerous diseases including type I and II diabetes mellitus, 6,7 SLE, 8 Sjögren's syndrome, 9 bone density and osteoporosis, [10][11][12] Alzheimer disease 13 and coronary heart disease. [14][15][16] The candidate gene approach has been widely used to analyse possible associations between genetic variants and autoimmune and inflammatory diseases, with the selection of genes by investigators based on a priori knowledge of disease pathogenesis and phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…were found to be associated with SLE by population-based case-control studies 18,19,20 . Although the initiating immunological event in SLE remains unknown, it has been shown that an imbalance is involved between depressed T H 1 cell cytokines, which promote cell-mediated immunity, and enhanced T H 2 cell cytokines, which support physiological cascade 21 . Cytokines are also known to be involved in the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Because the Hep3B cell line originates from human hepatocellular carcinoma and IL-6 is primarily synthesized in the liver, it is an appropriate cell line for this purpose. To replicate the Hep3B cell line results, we also tested the promoter activity in the HeLa cell line from human cervical carcinoma 21,23 . The promoter reporter structure carrying the -278 C allele displayed higher promoter activity than the structure carrying the -278 A allele in Hep3B cells and HeLa cells.…”
Section: Discussionmentioning
confidence: 99%